Sales success - Tracy, Brian (Brian Tracy success library., 2015)
The difference between top sales professionals and their less successful peers is that they perform just a little bit better in certain critical areas. In this compact and convenient guide, sales trainer extraordinaire Brian Tracy reveals how anyone can excel in these key capabilities. Packed with proven strategies and priceless insight, this book reveals how to identify competitive advantage; develop a sense of urgency and make every minute count; find and quickly qualify prospects; create rapport and build trust; understand the three keys to persuasion; master the elements of an effective pr.